THE CORRELATION BETWEEN MEAN ATERIAL PRESSURE AND BLEEDING VOLUME WITH THE NATIONAL INSTITUTE OF HEALTH STROKE SCALE (NIHSS) SCORE FOR INTRACEREBRAL HEMORRHAGE PATIENTS - Shonia Syvafiftyan Rosaline; Hermina Sukmaningtyas; Arinta Puspita Wati; Sukma Imawati (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
ABSTRACT Introduction: Intracerebral hemorrhage refers to primary, spontaneous, and non- traumatic bleeding that occurs in the brain parenchyma. Intracerebral hemorrhage accounts for approximately 10-20% of all stroke. The most common risk factor for non-traumatic hemorrhagic stroke is hypertension. The increase in Mean Arterial Pressure leads to the incidence of intracerebral hemmorhage. The NIHSS is a systematic assessment tool that quantitatively measures stroke associated with neurologic deficits. Neurological deficits that occur in intracerebral hemorrhage occur because blood enters the brain parenchyma. The incoming blood was measured by the Automatic Volume Method (software volume evaluation), namely the calculation of volume by computer software on the CT Scan tool.Aim: To determine the correlation between Mean Arterial Pressure and bleeding volume with NIHSS score in intracerebral hemorrhage patients.Methods: The research design used in this study was cross sectional. The sample of this study was 40 research subjects using purposive sampling, this study has independent variables, namely Mean Arterial Pressure and bleeding volume, while the dependent variable is the NIHSS score (National Institute of Health Stroke Scale). This study conducted an analysis using Spearman's.Results: : The results of this study indicate that there is no significant relationship between bleeding volume and NIHSS score (p = 0,157, r = 0,228) and there is no significant relationship between MAP and NIHSS score (p = 0,268, r = -0,179)Conclusion: There is no statistically significant relationship between Mean Arterial Pressure and bleeding volume with the NIHSS scoreKeywords: Mean Arterial Pressure, Bleeding Volume, National Institute of Health Stroke Scale, Intracerebral Hemorrhage